Chemical Compound Profile of Bajakah Kalalawit (Uncaria gambir Roxb) Stem Extract Using Liquid Chromatography High-Resolution Mass Spectrometry - Fawaid, Ainun; Mahfudh, Nurkhasanah (Borneo Journal of Pharmacy, 2025)
Uncaria gambir Roxb., commonly known as Bajakah Kalalawit, is a plant endemic to Kalimantan, Indonesia, with potential medicinal properties. While previous studies have investigated the phytochemical composition of U. gambir leaves, limited information exists regarding the constituents of its stem extract. This study aimed to comprehensively characterize the chemical composition of U. gambir stem extract using Liquid Chromatography-High Resolution Mass Spectrometry (LC-HRMS). Ethanol (96%) was employed as the solvent for maceration extraction (1 : 5, plant material : solvent ratio) for three days. Subsequently, the dried extract was subjected to LC-HRMS analysis. Compounds with an Area Under the Curve (AUC) value greater than or equal to 1% were considered as major constituents. The results revealed the presence of 18 distinct chemical compounds in the U. gambir stem extract, providing valuable insights into its phytochemical profile and laying the foundation for further investigations into its potential pharmacological activities.